2006
DOI: 10.1093/mutage/gel053
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects induced by formaldehyde in human blood and implications for the interpretation of biomonitoring studies

Abstract: Formaldehyde (FA) was tested for its genotoxicity in human blood cultures. We treated blood samples at the start of the culture to follow FA-induced DNA damage (DNA-protein crosslinks, DPX), its repair and its genetic consequences in form of sister chromatid exchanges (SCE) and micronuclei (MN). Our results clearly indicate that DPX (determined by the comet assay) are induced at FA concentrations of > or =25 microM. DPX induced by FA concentrations up to 100 microM are completely removed before lymphocytes sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 27 publications
0
46
2
Order By: Relevance
“…Several reports investigated the extent of chro- (13), it is still frequently used in histopathology laboratories worldwide as a fixative and tissue preservative. Occupational exposure to formaldehyde was found to increase the frequency of CATot, SCE, and micronuclei in PBL in a number of studies (3,6,(8)(9)(10), probably due to a long-term effect of the low doses that reach blood cells. Despite the fact that formaldehyde exposure was associated with lower frequencies of CATot, CTA, and CSA than exposure to anesthetics and antineoplastic drugs in our population, formaldehyde represents a serious health risk particularly as the frequencies of chromatid and chromosome exchanges were three-fold higher among the formaldehyde-exposed workers than the controls.…”
Section: Musak Et Almentioning
confidence: 99%
“…Several reports investigated the extent of chro- (13), it is still frequently used in histopathology laboratories worldwide as a fixative and tissue preservative. Occupational exposure to formaldehyde was found to increase the frequency of CATot, SCE, and micronuclei in PBL in a number of studies (3,6,(8)(9)(10), probably due to a long-term effect of the low doses that reach blood cells. Despite the fact that formaldehyde exposure was associated with lower frequencies of CATot, CTA, and CSA than exposure to anesthetics and antineoplastic drugs in our population, formaldehyde represents a serious health risk particularly as the frequencies of chromatid and chromosome exchanges were three-fold higher among the formaldehyde-exposed workers than the controls.…”
Section: Musak Et Almentioning
confidence: 99%
“…Indeed, in a few subjects no change in the amount of sperm DNA fragmentation was observed after sperm exposure to FA and in some semen samples the treatment paradoxically appeared to decrease the level of sperm DNA fragmentation, likely due to the loss of a fraction of fragmented cells. At micromolar doses, FA exerts a genotoxic action in somatic cells, including induction of DNA-protein crosslinks and DNA breakage Schmid and Speit 2007]. Such doses are much smaller than those used to fix cells (molar concentrations) and allow survival of the cells which are then able to repair the damage induced by FA Schmid and Speit 2007].…”
Section: Tunel: Principles and Type Of Damage Detectedmentioning
confidence: 99%
“…At micromolar doses, FA exerts a genotoxic action in somatic cells, including induction of DNA-protein crosslinks and DNA breakage Schmid and Speit 2007]. Such doses are much smaller than those used to fix cells (molar concentrations) and allow survival of the cells which are then able to repair the damage induced by FA Schmid and Speit 2007]. Molar concentrations obviously kill the cells, but preserve the native structure of somatic chromatin without extracting nucleoproteins [Hendzel et al 1997;Kozubek et al 2000].…”
Section: Tunel: Principles and Type Of Damage Detectedmentioning
confidence: 99%
“…Formaldehyde's mutagenic mode of action is quite well understood and it has been shown that formaldehyde predominantly acts by a clastogenic and not by an aneugenic mode of action (9)(10)(11). It is generally accepted that the induction of aneuploidy is a so-called indirect mechanism of genotoxicity due to an interaction with redundant non-DNA targets (e.g., tubulin; ref.…”
Section: Does Formaldehyde Induce Aneuploidy?mentioning
confidence: 99%